Back to the future of viruses: a case of triple coinfection caused by respiratory syncytial virus, human coronavirus OC43, and rhinovirus. (May 2023) - Davido, Benjamin; Jaffal, Karim; Gault, Elyanne; Bourlet, Stephane; Beaune, Sebastien
Highlights: Respiratory syncytial virus can cause severe infection in adults not only in children. Coinfection increases the burden of respiratory disease. Molecular testing is associated with an increased prevalence of coinfections. Abstract: We present the case of an 81-year-old man, who was immunocompetent, who was admitted to the hospital with symptoms of fever and dyspnea suspected to be caused by COVID-19. Further examination revealed a triple coinfection, as determined by multiplex polymerase chain reaction testing, caused by the respiratory syncytial virus, human coronavirus OC43, and rhinovirus. Upon auscultation, diffuse wheezing without crackles was detected. After ruling out the possibility of acute heart failure with pulmonary edema, the patient was treated with nebulization of terbutaline for a period of 72 hours. This case serves to demonstrate the potential dangers of lifting barrier measures, such as mandatory face masks in high-risk areas, during the fall-winter season. In addition, it highlights the challenges that may arise in the post-COVID-19 era because reliance on flu vaccinations alone may not be sufficient.